India-Pakistan Crisis : A New International Factor - Suryanarayana, Pisupati Sadasiva (2019)
India’s “counter-terrorism” strike inside Pakistan and their brief military exchanges have brought into focus China’s apparent stake in the stability of Indo-Pakistani relations.